2007
DOI: 10.1002/bem.20392
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced secretion of prostaglandin E2 from osteoblasts by exposure to a strong static magnetic field

Abstract: Exposure to static magnetic fields (SMFs) has been reported to promote osteoblast differentiation in vitro, and increase bone formation in vivo and in clinical studies. Prostaglandins respond early to exogenous mechanical loading, and play an important role in bone formation. In this study, we investigated whether exposure to a strong SMF affects prostaglandin E(2) (PGE(2)) secretion from a mouse osteoblastic cell line, MC3T3-E1. We also investigated the PGE(2)-synthesizing enzyme, cyclooxygenase 2 (Cox-2), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…We previously reported that magnetic field gradient and/or the product of magnetic field gradient and magnetic flux density played a critical role in the effects on biological systems [Hirose et al, 2003;Sakurai et al, 2008b]. In this study, we also detected the effects of magnetic field gradient and/or the product of magnetic field gradient and magnetic flux density, not magnetic flux density, on insulin secretion.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We previously reported that magnetic field gradient and/or the product of magnetic field gradient and magnetic flux density played a critical role in the effects on biological systems [Hirose et al, 2003;Sakurai et al, 2008b]. In this study, we also detected the effects of magnetic field gradient and/or the product of magnetic field gradient and magnetic flux density, not magnetic flux density, on insulin secretion.…”
Section: Discussionsupporting
confidence: 59%
“…In this study, to evaluate the effects of exposure to strong SMF on insulin-secreting cells, we cultured INS-1 cells under exposure to sham and SMF conditions, and analyzed insulin secretion, mRNA expression, glucosestimulated insulin secretion, insulin content, cell proliferation, and cell number. We exposed the cells to SMF for 0.5 or 1 h, because MRI diagnosis is usually performed within 1 h. We previously reported that strong SMF affected the assembly pattern of smooth muscle cells [Iwasaka et al, 2003] and osteoblasts [Kotani et al, 2000;Iwasaka and Ueno, 2005], depending on the magnetic flux density, and gene expression in HL-60 cells [Hirose et al, 2003] and prostaglandin E 2 secretion from osteoblasts by exposure to a high magnetic field gradient, but not by exposure to a high magnetic flux density [Sakurai et al, 2008b]. Therefore, we evaluated the effects of strong SMF from the viewpoint of magnetic flux density and magnetic field gradient in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, this effect of EMF on COX‐2 and PGE 2 expression has been demonstrated also for other cell types such as fibroblasts 38 . However, there are also contrasting data in the literature, demonstrating an upregulation of PGE 2 , probably due to the different types of magnetic fields and cells used 39 …”
Section: Discussionmentioning
confidence: 90%
“…Previous studies examining the effects of SMF on MSCs have also supported this hypothesis [Chuo et al, ; Kim et al, ]. Moreover, Sakurai et al [] reported that 10 T exposure alone had no effect on prostaglandin E2 secretion in osteoblasts, whereas a strong magnetic field (6 T) with a high gradient (41.7 T/m) showed progressive effects. Kotani et al [] reported that 8 T SMFs with a field gradient (approximately 4 T/100 mm) enhanced osteogenesis in vitro and in vivo [Kotani et al, ].…”
Section: Discussionmentioning
confidence: 79%